rationalise the above
Attachments:
![](https://hi-static.z-dn.net/files/d33/2433b62f25f4232665309bce78f0f48e.jpg)
Answers
Answered by
1
Solution:
Given
3/(√5+√2) + 7/(√5-√2)
= [3(√5-√2)+7(√5+√2)]/[(√5+√2)(√5-√2)]
= [3√5-3√2+7√5+7√2]/[(√5)²-(√2)²]
= [10√5+4√2]/(5-2)
=(10√5+4√2)/3
Or
= (2/3)[5√5+2√2]
••••
kblavanya97:
more confusion
Answered by
1
Hey !
Refer the below attachment !
Thanks !
Attachments:
![](https://hi-static.z-dn.net/files/d0e/34c032a0ad34fe514612195753edcf3e.jpg)
Similar questions